Expression of insect α6-like nicotinic acetylcholine receptors in Drosophila melanogaster highlights a high level of conservation of the receptor:spinosyn interaction. (September 2015) - Perry, Trent; Somers, Jason; Yang, Ying Ting; Batterham, Philip
Abstract: Insecticide research has often relied on model species for elucidating the resistance mechanisms present in the targeted pests. The accuracy and applicability of extrapolations of these laboratory findings to field conditions varies but, for target site resistance, conserved mechanisms are generally the rule rather than the exception (Perry et al., 2011 ). The spinosyn class of insecticides appear to fit this paradigm and are a pest control option with many uses in both crop and animal protection. Resistance to spinosyns has been identified in both laboratory-selected and field-collected pest insects. Studies using the model insect, Drosophila melanogaster, have identified the nicotinic acetylcholine receptor subunit, Dα6 as an important target of the insecticide spinosad (Perry et al., 2007; Watson et al., 2010 ). Field-isolated resistant strains of several agricultural pest insects provide evidence that resistance cases are often associated with mutations in orthologues to Dα6 (Baxter et al., 2010; Puinean et al., 2013 ). The expression of these receptors is difficult in heterologous systems. In order to examine the biology of the Dα6 receptor subunit further, we used Drosophila as a model and developed an in vivo rescue system. This allowed us to express four different isoforms of Dα6 and show that each is able to rescue the response to spinosad. Regulatory sequences upstream of the Dα6 gene able to rescue the resistance phenotype were identified. Expression of other D. melanogaster subunits revealed that the rescue phenotype appears to be Dα6 specific. We also demonstrate that expression of pest insect orthologues of Dα6 from a variety of species are capable of rescuing the spinosad response phenotype, verifying the relevance of this receptor to resistance monitoring in the field. In the absence of a robust heterologous expression system, this study presents an in vivo model that will be useful in analysing many other aspects of these receptors and their biology. Graphical abstract: Highlights: An in vivo system for characterising α6 receptor biology was developed. Individually expressed Dα6 isoforms are capable of restoring a response to spinosad. Specific expression patterns of Dα6 play an important role in the lethal effects of spinosad in Drosophila melanogaster . Pest insect α6-like subunits are capable of mediating a response to spinosad when expressed in D. melanogaster .